Effects of probiotics consumption and resistance exercise on bone metabolism markers in physically inactive young males / Nur Syazwani Ibrahim ... [et al.] - Ibrahim, Nur Syazwani; Muhamad, Ayu Suzailiana; Chen, Chee Keong; Ooi, Foong Kiew (Universiti Teknologi MARA, 2022)
This study aims to investigate the effects of probiotics supplementation and resistance exercise on bone metabolism markers and parathyroid hormones in physically inactive young men. Fourty-one healthy participants completed the study.